Köse Dağları (Ağrı) florası - Bakır, Yakup (My University, 2003)
KÖSE DAĞLARI (AĞRI) FLORASI Bu floristik çalışma Eleşkirt ilçesinin (Ağrı) 10 km kuzeyinde bulunan Köse Dağlarında yapılmıştır. Köse Dağları Eleşkirt ilçesinin sınırları içersinde bulunur ve rakımı 1600 ile 3439 m. arasında değişir. Çalışma alanı B9 karesine girmektedir. 2001 ile 2002 yılları arasında çalışma alanından toplanmış bulunan 1456 bitki örneğinden 46 familyaya ait 211 cinse bağlı 428 takson teşhis edilmiştir. Teşhis edilen taksonların 109'nun B9 karesi için yeni kayıttır. Teşhis edilen taksonların 37 tanesi endemiktir.. Taksonların %30,2 İran-Turan, %11,2'sini Avrupa-Sibirya, %3,9 Akdeniz orijinlidir. Geniş yayılışlı taksonların oranı %11,2 Orijini bilinmeyen taksonların oranı %43,5'tir. Ençok üyesi bulunan familyalar şunlardır; Asteraceae 62 (%14,4), Lamiaceae 44 (%10,2), Caryophyllaceae 38 (%8,8), Poaceae 30 (%6,9), Brassicaceae 27 (%6,3), Fabaceae 24 (%5,6), Rosaceae 22 (%5,1), Ranunculaceae 16 (3,7), Liliaceae 16 (%3,7), ve Boraginaceae 15 (%3,5)'dir. Haziran-2003Ya

FLORA OF THE KOSE MOUNTAINS (AGRI) This floristic research was carried out on the Köse Mountains which lies 10 km north of Eleşkirt Town (Agrı). Köse Mountains lies 10 km. north of the Eleşkirt Town (Ağrı) and within the frontiers of Eleskirt Town and its. altitude varies between 1600-3439 meters. The study area is within the B9 square 428 taxa in 211 genera belong 46 families were determined from 1456 plant samples which collected from the study area between 2001-2002 years. 109 of the determined taxa are new record for the B9 square. 37 of the determined taxa are endemics. 30,2 % of the taxa are orijinated from Irano-Turanian, 11,2 % are orijinated from Euro-Siberian and 3,9% are orijinated Mediterenean region. The ratio ot the widespread taxa is 12,2 % whilst, the ratio of the unknown taxa is 43,5 %. The families which have the most taxa numbers are as follows ; Asteraceae 62 (14,4%), Lamiaceae 44 (10,2 %), Caryophyllaceae 38 (8,8 %), Poaceae 30 (6,9 %), Brassicaceae 27 (6,3 %), Fabaceae 24 (5,6 %), Rosaceae 22 (5,1 %), Ranunculaceae 16 (3,7 %), Liliaceae 16 (3,7 %), Boraginaceae 15 (3, 5 %). June-2003Yakup B
Keywords: Botanik_Türkiye_Köse Dağları (Ağrı)